The rekhta of architecture: the development of ‘Islamic’ art history in Urdu, c.1800-1950 - Nile Green (Journal of Art Historiography, 2023)
This essay offers the first survey of architectural history after the Muslim conquests in the Indian Subcontinent in Urdu, the major Muslim literary language of colonial India. Contributing to the history of art history in non-European contexts, the essay traces the emergence of a deliberately ‘Islamic’ art history as the outcome of intellectual exchanges between Indian, European, and Middle Eastern authors. Reflecting this mixed provenance, the popular and scholarly texts examined here are termed ‘architectural rekhta’ by using the old name for Urdu (Rekhta: ‘mixed’). In apt architectural metonymy, ‘Rekhta’ was renamed ‘Urdu’ in homage to the Urdu-e Mu‘ala (or Red Fort of Delhi), revealing a conceptual link between the palace of the last Mughal emperors and Urdu as its language based on the centrality of buildings to Indo-Muslim cultural memory. Consequently, when colonial Muslim authors combined elements of European practice with their own concerns to produce their ‘mixed’ mode of art historical writing, architecture became their primary focus. In line with the themes of this special issue of the JAH, this approach examines the ‘post-Persianate’ cultural memory of Indian art of the Islamic period.